2
by tssuyambulingam
after solving it,my x is going to be cancelled out
try it once pls
your question's statement is false.plzz type clear statement

2015-04-25T12:24:32+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
25^x-1 = 5^(2x-1) - 100
⇒ 5^2x-2 = 5^(2x-1) - 100
⇒ 5^2x-2 - 5^2x-1 = -100
⇒ 5^2x [ 5^-2 - 5^-1] = - 100
⇒ 5^2x [ 1  -  1 ]  = - 100
25    5
⇒ 5^2x [ 1 - 5]  = - 100
25
⇒ 5^2x [ -4 ] = - 100
25
⇒ 5^2x [-4] = -100 * 25
⇒ 5^2x = 100 * 25     [ - * - = +]
4
⇒ 5^2x = 625
⇒ 5^2x  = 5^4
so, ⇒  2x = 4
⇒  x = 2
:)
what
what is meanig of akka?
sister
ohk....
2015-04-25T16:42:53+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
We need to bring together the terms containing x.  Then constant terms on the other side.  Then simplify by performing the addition/subtraction/multiplication.

done.